A User’s Guide to the Nestle–Aland 28 Greek New Testament. By David Trobisch - Elliott, J. K. (The journal of theological studies, 2014)
This little guide with its ungrammatical title parallels the author’s Die 28. Auflage des Nestle-Aland: Eine Einführung (Deutsche Bibelgesellschaft) but with biblical samples now taken from the NSRV and NIV rather than the Lutherbibel or the Zürich Bible. In a few cases (e.g. on conjectures) the German text is fuller, or is more accurate (e.g. when describing the location of Codex Sinaiticus [cf. German p. 28 with ET p. 20])., Trobisch aims at two audiences. One is students—be they complete beginners who even need to be taught the Greek alphabet (pp. 8–11), and one wonders if enquirers at that stage are ready to open a Greek testament, or those with some Greek.